2019
DOI: 10.1186/s12906-019-2707-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, and health- and sociodemographic associations for visits to traditional and complementary medical providers in the seventh survey of the Tromsø study

Abstract: BackgroundPatient-centered culturally sensitive health care (PC-CSHC) has emerged as a primary approach to health care. This care focuses on the cultural diversity of the patients rather than the views of the health care professionals. PC-CSHC enables the patient to feel comfortable, respected, and trusted in the health care delivery process. As users of traditional and complementary medicine (T&CM) rarely inform their conventional health care providers of such use, the providers need to identify the users of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…This will increase health care providers’ general knowledge of CAM use among their patients, and further help them to increase their knowledge of the most commonly used therapies and how they might interact with treatment they offer themselves to avoid negative interactions between CAM use and conventional care. As CAM users are people who express health care needs beyond ordinary public health care in Norway, health care providers need to identify them to be able to provide them with patient-centred health care in an open-minded, non-judicial way [ 36 ]. To be able to do this, earlier research has urged the need for more detailed information of the users and their reason for using CAM [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will increase health care providers’ general knowledge of CAM use among their patients, and further help them to increase their knowledge of the most commonly used therapies and how they might interact with treatment they offer themselves to avoid negative interactions between CAM use and conventional care. As CAM users are people who express health care needs beyond ordinary public health care in Norway, health care providers need to identify them to be able to provide them with patient-centred health care in an open-minded, non-judicial way [ 36 ]. To be able to do this, earlier research has urged the need for more detailed information of the users and their reason for using CAM [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAM providers offer their services mostly complementary to conventional treatment [ 35 ]. With few exceptions, and mainly in specific disease groups, CAM use in Norway has been reported as frequency and associations of total CAM use rather than for specific therapies [ 3 , 10 , 36 ]. We have therefore limited knowledge of which therapies, natural products, and self- help techniques that are used in Norway, and for what purpose people use the therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for this discrepancy might be that we included traditional medicine (TM) in our study, and that users of TM are known to have other associations for use than CM modalities not part of the country’s own tradition. As mentioned in the background section are users of TM older, have lower socioeconomic status and more severe health complaints than users of CM [26].…”
Section: Discussionmentioning
confidence: 99%
“…This lack of communication can increase the risk of negative interaction between T&CM and conventional cancer care as herbal medicine, used by 18% of the participants with cancer at present, is known to interact with conventional cancer treatment. Another study separating users of traditional medicine from users of other complementary therapies [26], found that the users of traditional medicine differed significantly from the users of other complementary modalities by being older and have lower socio-economic status. We found in addition that men with cancer was just as likely to use TM as women were.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation